Pengaruh Dana Alokasi Umum dan Dana Alokasi Khusus Terhadap Tingkat Kemiskinan di Kabupaten Simalungun - Rado Damanik; Darwin Damanik; Daniel Collyn (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2026)
Poverty is one of the most complex and pressing social and economic issues in Indonesia, particularly in rural and semi-rural areas such as Simalungun Regency. The objectives of this study are, first, to determine the impact of DAU and DAK on poverty levels in Simalungun Regency during the 2006–2025 period. The methods used are descriptive and quantitative, utilizing secondary data obtained from the Central Statistics Agency (BPS) of Simalungun Regency for the years 2006–2025, along with an analysis technique employing Ordinary Least Squares (OLS) Multiple Linear Regression. The results of this study are (1). The General Allocation Fund (DAU) variable has a negative and significant effect on the poverty rate in Simalungun Regency; (2). The Special Allocation Fund (DAK) variable has a negative but insignificant effect on the poverty rate in Simalungun Regency; (3). Simultaneously, the General Allocation Fund (DAU) and Special Allocation Fund (DAK) variables have a significant effect on the Poverty Rate in Simalungun Regency; and (4). The R-squared (R²) value is 0.738, so it can be concluded that the General Allocation Fund (DAU) and Special Allocation Fund (DAK) variables can explain 73.80% of the Poverty Rate in Simalungun Regency, while the remaining 26.20% can be explained by factors outside the scope of this study